PERANCANGAN FASILITAS MAL PELAYANAN PUBLIK UNTUK MENINGKATKAN PELAYANAN TERPADU SATU PINTU DI KABUPATEN BOGOR - Noorhayati, Susanti; Suryati, Adelina (Bussman Journal : Indonesian Journal of Business and Management, 2023)
The Public Service Center is the third integrated service renewal service and is considered the latest innovation in improving the best services in the community. This is an advancement in optimizing central and local government services, state/local enterprises and non-government/private enterprises in one building. . The first set of integrated services in Indonesia is One Stop Integrated Services (PTSA). Since then, the second update has been transformed into a one-stop comprehensive service (PTSP). The Mall of Public Service (MPP) is the realization of a non-profit office that provides integrated services in one building and simplifies administration and other benefits in a simple, secure, fast and scalable manner. (Ahmed et al., 2021). The Public Service Mall is designed to help the public more effectively and efficiently provide goods, services and management of licensed and non-licensed documents. The purpose of MPP Bogor Regency Design Facility is to increase the satisfaction index of the Municipality for state services for processing permit and non-permit administrative documents and other purposes. The MPP facilities are designed to ensure that the community can continue to derive comfort from service activities under all circumstances, including during peak traffic hours, even when many people visit the MPP in Bogor County